Rubrics on the Fly: Improving Efficiency and Consistency with a Rapid Grading and Feedback System - Adam C. Moyer; William A. Young II; Gary R. Weckman; Clarence (Red) Martin; Ken Cutright (Journal of Teaching and Learning with Technology, 2015)
Many learning management systems (LMS) used in higher education provide customizable rubrics that aid in the process of grading and providing feedback for many forms of assessments commonly used by educators today. Rapid Grade is a grading and feedback feature built into a non-commercialized LMS developed by a large, public, Midwestern university in the United States. In this research, Rapid Grade was compared to a grading and feedback system found in one of the most utilized LMS found in higher education. It should be noted that the name of this particular LMS is not named. Using the Technology Acceptance Model to validate that Rapid Grade empirically improves upon existing methods, survey results indicate that Rapid Grade is a significant improvement in terms of ease of use and usefulness when grading and providing feedback for a given assessment. The Rapid Grade framework as well as the specific results of the TAM is presented.